2019
DOI: 10.1371/journal.pmed.1002788
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of a social protection policy on tuberculosis treatment outcomes: A prospective cohort study

Abstract: Background Tuberculosis (TB) still represents a major public health problem in Latin America, with low success and high default rates. Poor adherence represents a major threat for TB control and promotes emergence of drug-resistant TB. Expanding social protection programs could have a substantial effect on the global burden of TB; however, there is little evidence to evaluate the outcomes of socioeconomic support interventions. This study evaluated the effect of a conditional cash transfer (CCT) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…This added further evidence to previous predictive modelling that demonstrated that global TB incidence would be reduced by 84•3% if poverty were eliminated; and implementation of social protection measures alone would reduce tuberculosis incidence by 76•1% [7]. Various recent studies have indeed shown that cash transfers to patients with TB might improve treatment outcomes [8][9][10][11].…”
Section: Introductionmentioning
confidence: 56%
“…This added further evidence to previous predictive modelling that demonstrated that global TB incidence would be reduced by 84•3% if poverty were eliminated; and implementation of social protection measures alone would reduce tuberculosis incidence by 76•1% [7]. Various recent studies have indeed shown that cash transfers to patients with TB might improve treatment outcomes [8][9][10][11].…”
Section: Introductionmentioning
confidence: 56%
“…A similar study in Argentina also indicated that those registered for the CCT program had a significant and positive effect on treatment adherence after controlling for socioeconomic and demographic variables (Klein et al 2019).…”
Section: Tuberculosis (Tb)mentioning
confidence: 76%
“…The consideration of societal topics should be better addressed in the education of sleep and respiratory physicians. Additionally, studies are needed to investigate the impact of health policy interventions on PAP adherence, as has been done for medications in vulnerable populations (34).…”
Section: Discussionmentioning
confidence: 99%